Risco a erosão na microbacia do Córrego Samambaia no município de Chapada dos Guimarães – MT - Ramos, Maria Cristina da Silva (2012)
Risk mapping has become an effective tool in the prevention of accidents that could result in economic losses and even life losses. In order to determine susceptibility to both sheet erosion and linear erosion, initially, a slope map was prepared based on the ASTER-DEM terrain numerical model, and slope classes were extracted for the various slopes using ARCGIS version 9.3 software. Susceptibility classes were defined for sheet erosion and linear erosion based on the slope maps and pedological maps, as well as on field notes. Susceptibility maps for sheet erosion and linear erosion were prepared. Based on those maps, the erosion risk was determined for the Samambaia catchment by means of a map that showed the following results: High Risk Areas – classes II and III of the linear erosion susceptibility map and all classes of the sheet erosion susceptibility map were grouped into this category. High risk areas are mainly characterized by headwater areas; they comprise the initial portion of the catchment, with a headwater stream area under intense occupation; headwater streams are completely degraded and veredas (headwater wetlands) are used as treading areas by the cattle to reach the water course. Low Risk Areas are steep-slope areas with very reduced utilization, where the vegetation is undergoing a process of natural regeneration; low risk areas are not under risk of erosion, and are free from any type of soil use. It is recommended that basin occupation should follow some precautions and practices in areas characterized as high erosion risk areas, such as: restricting occupation of areas adjacent to the headwaters of streams that comprise the basin’s drainage network, and adopting soil use conservation techniques.